KOMUNIKASI MATEMATIS SISWA SMA DALAM MENYELESAIKAN SOAL LOGARITMA DITINJAU DARI KEMAMPUAN MATEMATIKA - Feriyanto, Feriyanto (Prodi Pendidikan matematika Universitas Islam Majapahit (UNIM), Mojokerto, Indonesia, 2018)
The demand to improve students' mathematical communication skills in solving problems is important in mathematics learning. With good mathematical communication skills, then a problem can be represented well and facilitated in its completion. The purpose of this researchs to describe the mathematical communication of high school students in solving logarithmic problems based on mathematical ability. The subjects of this research were 3 students of class X IPA 6 SMAN 1 Puri with details of 1 student with the highest mathematics ability, 1 students with medium mathematics ability, and 1 students with the lowest math ability. The selection of the subject of this research based on mathematics test, and the results of consultation with the mathematics teacher. Subjects were given the first mathematical communication test, then conducted interviews to dig deeper mathematical communication. After 2 weeks, they given the second mathematical communication  then interviewed.